The Autoethnographic Genre and Buddhist Studies: Reflections of a Postcolonial Western Buddhist' Convert - Ng, Edwin (Australian religion studies review, 2012)
Is there a place for autoethnography in Buddhist Studies, particularly the emerging discourse described as Buddhist critical-constructive reflection? Predicated on a commitment to be always mindful of the colonial, Orientalist heritage of Buddhist Studies and the role of the subject in its own discourse, Buddhist critical-constructive reflection brings together the sacred and scholarly pursuits of the Buddhist practitioner-scholar to develop new interfaces between Buddhism, academia, and society. This article explores the possible contribution of autoethnography by sharing the autoethnographical reflections of the author, who despite growing up in Singapore where Buddhism forms a part of his ancestral, cultural heritage, only embraced it as a life-pursuit after discovering in Australia Western interpretations of Buddhist doctrine and practice.